PEMANFAATAN DAUN PALADO (Agave sp) DALAM PROSES PEMBUATAN VIRGIN COCONUT OIL (VCO) - Nuryanti, Siti; Rahmawati, Sitti; U.B., Sitti Nadira (Jurnal Akademika Kimia, 2013)
VCO lately has been used in medical area especially as a medicine for diabetes mellitus, obesity, cholesterol, heart, osteoporosis and can be used to cure diseases that caused by microbial and fungal. VCO also acts as antibiotic because it contains lauric and oleic acid. The availability of VCO materials in Indonesia is abundant, therefore to be developed as a medicine substance, the process of VCO making should be without any chemical material and high heating. The aim of this research is the utilization of palado leaves in the making process of VCO as well as to determine its quality. The method used in this research is the preparation of palado leaves fiber sample, preparation of cream coconut milk with coconut, the making of VCO fermentative for 20 hours and quality test for the VCO made with extra palado leaves by using parameters of colour, smell, the acid number, peroxide number, water content, refractive index and specific gravity, as a comparison is a commercil VCO (Celebes brand). Data analysis used is descriptive qualitative. The research result shows that VCO made with extra palado leaves has clear colour, normal smell, savory taste, while its acid number is 0.4 mg/g, peroxide number is 1 meq/g, water content is 1%, refractive index is 1.44804 and density is 0.888 g/ml. On the other hand, VCO Celebes has clear colour, normal smell and savory taste, while its acid number is 0 mg/g, peroxide number is 0 meq/g, water content is 0%, refractive index is 1.44803 and density is 0.892 g/ml. The conclusion of this research is that the palado leaves can be used in the making process of VCO and the VCO produced is suitable to APCC standard.